(untitled) (Al-Qamar, 2019)
Among the great iconic names of Hadith scholars, is the name of Abu Abdullah Muhammad bin Abdullah Al Hakim. He is credible and exemplary with regards to his knowledge, humility and God consciousness. His esteemed position in Hadith sciences is an undeniable reality. He was a “Hafiz”, “Thabt”, “Arif Birrijal” and an expert of “Ilal Al Hadith”. He had several teachers, and likewise he had a vast range of students, who may be regarded as his spiritual progeny. Imam Hakim wrote several books and spent all his capabilities throughout his life in collecting precious gems of knowledge, so much so that his books number more than four thousand. Among these books, is “Al Mustadrak”, which he has compiled according to the chapters of “Fiqh”, keeping in mind the order followed by Bukhari and Muslim, because he claims to have compiled the Ahadith which are according to the conditions of “Sahihain” but are not found in them. Imam Hakim’s obvious inclination was towards the Shaf’i school of thought. He has also categorized the narrators as authentic and weak, and has scrutinized them, however he is one of those hadith scholars who are known for their leniency in scrutiny of hadith narrators. Like Ibn Khuzayma and Ibn Hibban, he too does not differentiate between Hassan and Sahih hadith. After completing al Mustadrak, he did not get a chance to review, elucidate or edit his work, therefore the book did not reach up to the expectations that were once attached to it. Anyhow, Imam Hakim was a dignified scholar, having a unique approach. When a man is sincere in his intentions and seeks help from Allah, He helps his slave in magnificent ways; and this is evident from the life of this honorable scholar.